Investigating the Geoenvironmental and Climatic Impacts on the Facades of Historical Houses in Killit (Dereiçi) Village, Mardin - Karataş, Lale; Dal, Murat (My University, 2023)
Killit (Dereici), which is largely abandoned today, is an Assyrian village thought to have a population of more than 20,000 spread around the world. The Kilit (Dereiçi) village of Savur stands out as a rare example in the world with its multi-identity structure. The street façades of this Assyrian village, which has such cultural importance, can be clearly seen today, due to various factors. The aim of the study is to investigate the damage patterns and the factors affecting the durability of Kilit (Dereici) street facades (Old Bazaar). For this purpose, observational detection method was used and the findings were presented based on the dictionary of stone deterioration patterns prepared by ICOMOS-ISCS,2008. As a result of the study, the most intense deteriorations observed on the street facades; cement-induced faulty repairs made between the joints of the stone blocks on the facades and ‘crack, disintegration, erosion, ‘missing part, discolouration’ on the stone surfaces exposed to climate impact for a long time.
Keywords: Restoration; disintegration; stone deterioration; Geoenvironmental and climatic impacts; Killit (Dereiçi) Village